Determinan Risiko Pembiayaan pada Bank Pembiayaan Rakyat Syariah (BPRS) di Indonesia Periode 2019-2021 - Rhamadhani, Devi Nur; Wafaretta, Vega (Politeknik Negeri Ambon, 2023)
The financing risk of Islamic People's Financing Banks (BPRS) in Indonesia needs special attention, because the high ratio of non-performing loans exceeds the maximum limit set by the Financial Services Authority (OJK) of 7%. Therefore, this study aims to examine the effect of financial ratios on the risk of BPRS financing in Indonesia for the quarterly period 2019-2021. These financial ratios (minimum capital ratios, profitability ratios, liquidity ratios, operational efficiency ratios and profit-sharing financing ratios) can then become a concern for BPRS so that they are managed properly as a basis for managing financing risk. The number of samples in this study was 1344 which were analyzed using panel data regression. This analysis shows that the previous period's capital adequacy acted as a reserve for BPRS, thereby encouraging banks to minimize financing risks. Meanwhile, increasing BPRS efficiency can reduce financing risk. Profit sharing financing with strict selection also has a negative effect on financing risk. Profitability and liquidity do not affect financing risk because the ability of BPRS to maintain profit performance varies and there are variations in risk exposure to customers that have no impact on financing risk. The implication of this research is that the BPRS needs to maintain financial ratios to comply with OJK regulations. In addition, the BPRS needs to maintain capital adequacy, efficiency, and the amount of financing disbursed so that financing risks are under control. In addition, good management of profit-sharing financing can be applied to other financing. Future research can develop research with other variables that affect the risk of BPRS financing in Indonesia.